APAKAH PROMOSI UNIVERSITAS TERMASUK PERTANGGUNGJAWABAN SOSIAL? - Erna Pasanda; Amiruddin; Darwis Said; Ratna Ayu Damayanti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
This study aims to determine whether the promotion carried out by the University, especially when student admission is a form of social responsibility. This research is a qualitative research with ethnometodology approach. The information used was the Chairperson of the UKI New Student Admissions Committee and who was in charge of University promotion. Research results prove that campus promotion is part of the University's initial social responsibility towards the community.